Green and Cost-Effective Extraction Techniques of Quercetin from Mixture of Nutraceuticals with Yield Analysis via Spectrophotometry and High-Performance Liquid Chromatography Methods. (18th May 2021) - Gamal, Mohammed; Abd-ElSalam, Heba-Alla H; Naguib, Ibrahim A; Al-Ghobashy, Medhat A; Zaazaa, Hala E; Abdelkawy, M
Abstract: Background: Extraction is the leading critical stage in the analysis of nutraceuticals. Ginkgo biloba (GB) has gained interest because of its therapeutic usages. Objectives: The aim was to develop four cost-effective extraction techniques for the extraction of quercetin from GB in a sachet containing a mixture of nutraceuticals. These techniques are solid-phase extraction (SPE), liquid–liquid extraction, inverted dispersive liquid–liquid microextraction, and the QuEChERS (quick, easy, cheap, effective, rugged, and safe) method. Method: Direct spectrophotometry was used to monitor the recovery of the standard quercetin throughout the optimization steps. The HPLC–UV method of analysis was optimized to quantify the yields from the extracts present in the complicated contents of the sachets. The present study was assessed by analytical Eco-Scale assessment (ESA) and the National Environmental Method Index (NEMI) for greenness in comparison with the literature. Results: SPE showed the best cleanup outcomes. ESA and NEMI showed an adequate greenness of the proposed extraction protocol. Conclusions: Quercetin (marker for GB) extraction from market nutraceutical sachets is considered an exemplar for analysis in the QC of nutraceuticals. Regarding the greenness results, the proposed method of extraction is better even with adequate greenness as the extraction was a one-step process, in comparison with multistep processes of previously published protocols. Accordingly, it is recommended for use in routine extraction and analysis of such nutraceuticals. Highlights: Four extraction protocols have been developed. For GB ternary-mixture sachets, proper recovery was obtained using C18 SPE. The assessment of greenness of the proposed protocol guaranteed the superiority of the presented method. Safer sorbents and chemicals are favored for use in routine extraction of nutraceuticals.